Perlindungan Hukum Bagi Kreditur Terhadap Pelaksanaan Eksekusi Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi No. 18/PUU-XVII/2019 (Studi Kasus Putusan Nomor 36/Pdt.G.S/2023/PN Pdg) - Sunny Halim, Kerenina; Suprapti, Endang (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Constitutional Court Decision No. 18/PUU-XVII/2019 was issued in response to a judicial review request concerning Article 15 Paragraphs (2) and (3) of Law No. 42 of 1999 on Fiduciary Security. This decision introduced new legal changes regarding the regulation and implementation of fiduciary collateral execution procedures, both before and after the ruling, as well as legal protection mechanisms for creditors when debtors commit default (fail to fulfill their obligations). This legal research employs a normative juridical approach. Based on the findings, the conclusion is as follows: The Padang District Court’s decision demonstrates inconsistency in the judges’ assessment of the legal aspects of fiduciary execution, particularly concerning the default clause and the enforcement of the Power of Attorney for Withdrawal. Although the debtor was proven negligent, the judge did not classify it as a default under Article 1243 of the Indonesian Civil Code. The judge also awarded damages without sufficient evidence and ordered the return of a down payment that was not the responsibility of the litigating party. This reflects weak application of the principles of legal certainty and justice in fiduciary security, which should be based on Law No. 42 of 1999 and Financial Services Authority Regulation (POJK) No. 35/2018. Furthermore, the change in execution mechanisms following Constitutional Court Decision No. 18/PUU-XVII/2019 has created legal uncertainty, as execution can now only be carried out with the debtor’s consent or through a court process. While this condition protects debtors, it is prone to misuse, potentially disrupting legal certainty and financial stability. Therefore, a balance of legal protection between creditors and debtors is essential to ensure justice and maintain the stability of the financial system.